Promosi Produk Akad Qord Al Hasan di Lembaga Keuangan Syariah - Saifuddin Zuhri (Fakultas Ekonomi dan Bisnis Islam, 2020)
Promotion of the qard al hasan contract product is the act of informing about the specifications of the qard al hasan contract product in an Islamic financial institution. The qard al hasan contract product is one of the financing products that LKS can do as a form of concern for the public who experience financial difficulties in doing business due to bankruptcy or bankruptcy. Qard al hasan is a benevolent loan that may not require profits or profits from the principal loan made by the LKS and the members. members only pay the principal loan to the LKS in accordance with the agreement.